2015
DOI: 10.1093/aepp/ppv018
|View full text |Cite
|
Sign up to set email alerts
|

Price Differences across Farmers’ Markets, Roadside Stands, and Supermarkets in North Carolina

Abstract: Whether direct farmer‐to‐consumer outlets compete with supermarkets on produce prices remains an empirical question; marketing costs are not consistently higher in one retail channel or the other. This study compared prices of 29 fruits and vegetables across North Carolina farmers’ markets, roadside stands, and supermarkets. Larger farmers’ markets had higher prices: three fruits and one vegetable were cheaper at a direct outlet, while four vegetables were cheaper at supermarkets. Weighting item prices by cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…This study has found evidence that traditional markets have significantly lower FV prices than supermarkets. Valpiani et al . (2015), however, found that FV prices in supermarkets and direct farmer-to-consumer retail outlets were not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…This study has found evidence that traditional markets have significantly lower FV prices than supermarkets. Valpiani et al . (2015), however, found that FV prices in supermarkets and direct farmer-to-consumer retail outlets were not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…We include per capita personal income (PCPI) (USDOC BEA, 2016) in log form to account for the effect of income on DTC sales. While there is some debate in the local foods literature regarding the effect of income on farmers markets sales, income does play a role in food purchases by households (Gregory & Coleman-Jensen, 2013;Low & Vogel, 2011;Valpiani et al, 2016). Next, we include a proxy for food access by using the share of people in a county who commute to work using public transportation (USCB, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The literature suggests that freshness and quality are principle reasons for purchasing local food; however, an overarching generalization that consumers will pay more for local foods cannot be drawn from studies that estimated price premiums (Martinez et al 2010. Prices at DTC outlets generally are comparable to prices at traditional retail outlets (e.g., Valpiani et al 2015).…”
Section: Incomementioning
confidence: 97%